The Effect of Changes in the Value of Conventional Interbank Transfers and Digital Banks in Technological Development - Fitri Kumala Sari; Yossy Fadly; Puja Rizqy Ramadhan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2022)
The digital revolution in the last decade has drastically changed the transaction behavior of economic agents. Consumption patterns are shifting to shopping on digital platforms and demanding an all-in-one payment method. From 2014 to 2021, Bank Indonesia noted that Indonesia experienced an increase in income. Even during the COVID-19 pandemic, many startups in Indonesia played a role in helping Indonesia's economic activities and stabilizing people's incomes. In addition, Bank Indonesia also helps Conventional Banks to compete with Startups that have become Digital Banks by creating an Open-Banking-based BI-Fast program. This program also helps Retail UMKM make it easier for the community to make payments at a cost of IDR 2500.